THE EFFECT OF PERSONALITY AND CLIMATE ORGANIZATION ON JOB SATISFACTION PRIVATE TEACHERS OF TECHNICAL HIGH SCHOOL - Achmad Fahrurrozziq; Bedjo Sujanto; Suryadi Suryadi (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
This aim of this research was to study the influence of personality, climate organization, on job satisfaction. The method used is a survey method with the type of explanatory research. The method used is this research was quantitative approach. Survey data collected 231 teachers. Data analysis using path analysis. Result, the high conducive organizational climate directly positively influences high job satisfaction, good personality will directly affect positively the organizational climate of the teachers. Based on the hypothesis testing that has been done, it can be described as the following research findings: (1) there is a positive direct influence of personality on job satisfaction, (2) there is a positive direct influence of climate organizations on job satisfaction, (3) there is a positive direct influence between personality on climate organizations.